2021
DOI: 10.3390/molecules26206142
|View full text |Cite
|
Sign up to set email alerts
|

Caryophyllene Oxide, the Active Compound Isolated from Leaves of Hymenaea courbaril L. (Fabaceae) with Antiproliferative and Apoptotic Effects on PC-3 Androgen-Independent Prostate Cancer Cell Line

Abstract: Cancer treatment frequently carries side effects, therefore, the search for new selective and effective molecules is indispensable. Hymenaea courbaril L. has been used in traditional medicine in South America to treat several diseases, including prostate cancer. Leaves’ extracts from different polarities were evaluated using the 3-(4,5-methyl-thiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) cell viability assay to determine the cytotoxicity in prostate p53-null cells, followed by bio-guided fractionations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…Hence, it was postulated that KPF would show high bioactivity in the anticancer and antimicrobial bioassays. Moreover, Kakadu plum and Illawarra plum have previously been shown to exhibit significant in vitro antioxidant, anti-inflammatory, and proapoptotic anticancer activity [ 6 , 7 , 8 , 9 , 10 ]. Furthermore, Kakadu plum fruit have the highest recorded concentrations of ascorbic acid of any fruit in the world [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it was postulated that KPF would show high bioactivity in the anticancer and antimicrobial bioassays. Moreover, Kakadu plum and Illawarra plum have previously been shown to exhibit significant in vitro antioxidant, anti-inflammatory, and proapoptotic anticancer activity [ 6 , 7 , 8 , 9 , 10 ]. Furthermore, Kakadu plum fruit have the highest recorded concentrations of ascorbic acid of any fruit in the world [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Germacrene D and bicyclogermacrene, other sesquiterpene hydrocarbons, have also been reported as cytotoxic agents against melanoma, leukemia, and colon cancer [ 31 , 32 ]. Caryophyllene oxide, a sesquiterpene oxygenated, caused apoptotic cell death in prostate cancer cells, as evidenced by depolarization of the mitochondrial membrane, morphological changes, and caspases activation [ 33 ]. Spathulenol, another sesquiterpene oxygenated, has been shown to be cytotoxic against melanoma, leukemia, and liver cancer cell lines [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Caryophyllene oxide is a small molecular compound that can be found in various plants ( Sanchez-Munoz et al, 2012 ; Monzote et al, 2018 ; Ibrahim et al, 2019 ). Recent studies indicated that it has an inhibitory effect on prostate cancer cells ( Delgado et al, 2021 ), and previous research linked its antitumoral mechanism to apoptosis and mitochondrial depolarization ( Delgado et al, 2021 ). However, the effect of caryophyllene oxide on ferritinophagy in hepatocellular carcinoma has never been reported and the precise mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Caryophyllene oxide is a small molecular compound found in a variety of plants ( Sanchez-Munoz et al, 2012 ; Monzote et al, 2018 ; Ibrahim et al, 2019 ). One study showed that caryophyllene oxide can improve mitochondrial membrane depolarization and trigger early and late apoptosis in PC-3 cells ( Delgado et al, 2021 ). Caryophyllene oxide has been found to have analgesic and anti-inflammatory effects ( Chavan et al, 2010 ), and it has inhibitory effects on different insect vectors ( Monzote et al, 2009 ; Moreno et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%